DETERMINING THE PRIORITY OF FISHING EQUIPMENT BASED ON HONESTYTHE ENVIRONMENT USING THE ANALYTIC HIERARCHY PROCESS IN TANAH MERAH VILLAGE,INDRAGIRI - Audina Agustin Syam; Nofrizal Nofrizal; Romie Jhonnerie (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbtracThis research was carried out from March 2019 to April at Tanah Merah Village, Tanah Merah District, Indragiri Hilir Regency, Riau Province. The purpose of this study is to determine the level of environmental friendliness of fishing gear operating in the waters of Tanah Merah Village and determine which fishing gear is a priority to be developed.The method used in this study is a survey method,where the author goes directly to the field to evaluate fishing gear such as gillnets, kurau nets, and togok operated by Tanah Merah fishermen.          Based on the results of environmental friendliness scores that from the results of interviews and identification of fishing gear directly, it was found that the higher score was on gillnet fishing gear (gillnet) followed by kurau and togok nets.Where the score of the level of friendliness for gillnets is 31, kurau nets 26,95, and togok 24,5.And the fishing gear that is the priority is gillnet with a weight value of 0,503345, then followed by fishing gear for kurau nets with a weight value of 0,337725 and togok fishing gear with a weight value of 0,158883.Keywords :environmental friendliness of fishing gear, fishing gear priority